Efficient fluoride adsorption by mesoporous hierarchical alumina microspheres. Issue 48 (28th April 2016) - Lanas, Sara Gràcia; Valiente, Manuel; Aneggi, Eleonora; Trovarelli, Alessandro; Tolazzi, Marilena; Melchior, Andrea
Abstract : Mesoporous Hierarchical Alumina Microspheres (HAM) with high efficiency for fluoride removal have been synthesized and characterized. Abstract : Mesoporous Hierarchical Alumina Microspheres (HAM) with high efficiency for fluoride removal have been synthesized and characterized. Two types of HAM, differing mostly in crystallinity, surface area and pore size have been obtained. Fluoride adsorption studies have been carried out by means of potentiometry and Isothermal Titration Calorimetry (ITC). The latter method has been applied for the first time to obtain direct determination of the adsorption enthalpy (Δ H ads ) of F − ion on HAM. The kinetics of the reaction revealed a two-step process for fluoride adsorption on the adsorbent material. The Δ H ads values obtained are clearly negative for the different samples investigated. Experimental adsorption data are well fitted by a Langmuir isotherm. The adsorption constant obtained for type A is 1 order of magnitude higher than for type B, showing that the synthetic protocol has a remarkable effect on this parameter. The highest defluoridation capacity reaches 26 mmol g −1 after 1 hour of equilibration for the amorphous HAM, which is higher than for other adsorbents reported in the literature.